Growth and quality of Garcinia humilis seedlings as a function of substrate and shading level - Barbosa da Silva, Bruna Luzia; Costa, Edilson; Silva Binotti, Flavio Ferreira da; Sabin Benett, Cleiton Gredson; Silva, Abimael Gomes da [UNESP] (Univ Federal Goias, 2018)
The successful establishment of a Garcinia humilis orchard depends on planting high-quality seedlings. This study aimed to evaluate the effects of the shading level (0 %, 18 % and 50 %) and substrate composition on the formation of G. humilis seedlings. Four substrates (S) were evaluated combining different proportions (v:v) of soil (SO), cattle manure (CM), commercial substrate (CS), sand (SA) and fine grain vermiculite (FV): S1 = 0 % SO + 45 % CM + 20 % CS + 20 % SA + 15 % FV; S2 = 15 % SO + 30 % CM + 20 % CS + 20 % SA + 15 % FV; S3 = 30 % SO + 15 % CM + 20 % CS + 20 % SA + 15 % FV; S4 = 45 % SO + 0 % CM + 20 % CS + 20 % SA + 15 % FV. The experiment was conducted in a completely randomized design in each environment, being the environments compared by a joint analysis. The G. humilis seedlings with the highest quality were obtained in the environment with a 50 % shading screen. G. humilis seedlings do not grow when exposed to full sunlight and, therefore, the seedling production of this species with direct solar radiation, without some shading level, should not be recommended. Different combinations from the mixture of soil, cattle manure, commercial substrate, sand and fine grain vermiculite may be used in the formulation of substrates for G. humilis seedlings.